(untitled) (Observatorio Económico, 2014)
Competition in the market of AFPs (pension fund administrators) was one of the central issues of the 2008 pension reform. However, five years after its implementation, it can be stated that its effects in this area were modest. Currently, the creation of a state-owned AFP is the main pro-competition initiative promoted by the government, and it lies at the center of a debate with supporters and detractors across all sectors of the economy. Continue reading...